2017
DOI: 10.1136/bjsports-2016-097372.316
|View full text |Cite
|
Sign up to set email alerts
|

Exercise Associated Hyponatremia (Eah) and Fluid Intake During the 2016 London Marathon

Abstract: BackgroundExercise-Associated Hyponatremia (EAH) is a potentially fatal condition during endurance exercise (Petzold et al, 2007). Excessive fluid intake over and above normal fluid losses is the most common risk factor in the development of EAH. A “drink to thirst” fluid regime is considered best practice (Hew-Butler et al, 2015).ObjectiveTo investigate fluid intake and changes in serum sodium concentrations ([Na]+) in runners during a marathonDesignProspective observational study.Setting2016 London Marathon.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Because most fluid replacement options are hypotonic, they remain inadequate replacement for solute loss At the 2016 London Marathon, change in serum sodium was inversely correlated with change in body mass and estimated fluid intake. 13 Previous studies have shown concern that NSAIDs can increase the risk of developing EAH. 8 In our study, although not significant, we found that slower, first time runners used more NSAIDs within the week leading up to marathon when compared with their faster counterparts.…”
Section: Discussionmentioning
confidence: 99%
“…Because most fluid replacement options are hypotonic, they remain inadequate replacement for solute loss At the 2016 London Marathon, change in serum sodium was inversely correlated with change in body mass and estimated fluid intake. 13 Previous studies have shown concern that NSAIDs can increase the risk of developing EAH. 8 In our study, although not significant, we found that slower, first time runners used more NSAIDs within the week leading up to marathon when compared with their faster counterparts.…”
Section: Discussionmentioning
confidence: 99%